Analisis Dampak Negatif Pengunaan Artificial Intelligence dalam Pendidikan - Hadi, Zainul; Ali, Moh. (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
Currently, technology has penetrated all aspects of human life. The world of education is no exception. The presence of technology has a significant positive impact on education. However, the presence of AI technology is also not free from challenges and problems. This study aims to analyze the adverse effects of using artificial intelligence in education. By using a qualitative approach with a literature study type, this research data was obtained from searching for sources of scientific articles spread across internet pages. The results of this study indicate that the use of artificial intelligence in education can decrease teacher function and role interaction between humans, erosion of student ethics and morals, and excessive dependence on AI, also resulting in the loss of learning.